El cuento en el desarrollo de valores - Caisaguano Moreano, Betty Elizabeth (2016)
The research on the story in the development of values in children, had like finality to achieve that through the narrative of tales is reached to get to the children, thus this research aim that children take awareness of living and educate in values by practicing values help them to live better and feel good in the environment that the children are, as well as they contribute in the intellectual, emotional and social development. The values such as friendship, sympathy, tolerance, patient, solidarity, respect among others values, are essential for a healthy development. The stories unlike any other form of children´s literature lead to discover values, identity and vocation, these are the ideal instrument for learning to overcome some linguistic and mental barriers, these have positive effects as the learners identify themselves with heroes of the narrative appropriating who were exited of the ideas and solutions proposal for the overcoming of earners’ problems, in the social, educative and familiar field in a creative, imaginative way and without any pressure for practicing them but rather that they make of the values a habit of life and development them for a better society. At “Numa Pomillo Llona” Educative Unit was achieved to verify that the lack of values is a theme that do not have any research with the final purpose of eradicate this lack, taking into account that it is an Institution of State and that have big needs and at the same time families that live in the puberty and devoted to work desisting the education of their children and for this reason the foment of values like principal foundations in their daily lives.